THE EFFECT OF FINANCIAL DISTRESS, COMPANY SIZE, CAPITAL INTENSITY AND LEVERAGE ON ACCOUNTING CONSERVATISM - Matthew Christian (Universitas Pelita Harapan, 2022)
The company's financial statements will describe the effectiveness of its management in managing company resources. Management can choose which accounting technique to use in the preparation of financial statements. One of the techniques that can be used is the accounting conservatism technique. The purpose of this study was to determine the effect of financial distress, firm size, capital intensity and leverage on accounting conservatism. The population in this study by period is Manufacturing companies listed on the Indonesia Stock Exchange in the period 2017 – 2019. The number of samples analyzed were 30 companies. The sample was taken by purposive sampling method where the data taken were selected using certain criteria. The analysis technique used was multiple linear regression analysis. The results of this study indicate that financial distress has no effect on accounting conservatism, firm size has no effect on accounting conservatism, capital intensity has no effect on accounting conservatism and leverage also has no effect on accounting conservatism.